Scaffolding-Based E-Book on Kamasan Wayang Painting for Fine Arts Material for Students with Intellectual Disabilities - Anggun Anggraini; Anak Agung Gede Agung; Didith Pramunditya Ambara (Universitas Pendidikan Ganesha, 2026)
The problem in fine arts learning for students with intellectual disabilities lies in their low painting skills, which are caused by the lack of instructional media that align with their characteristics and learning needs. This study aims to develop, evaluate the feasibility, and examine the effectiveness of a scaffolding learning-based e-book on Kamasan Wayang painting in improving students’ painting skills. This study employed a Research and Development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The participants of the study were students with intellectual disabilities involved in individual and small group trials. Data were collected through expert validation sheets and performance assessment instruments to measure students’ painting skills. Data analysis techniques included descriptive quantitative analysis and a paired sample t-test to determine the effectiveness of the product. The results indicate that the developed e-book is highly feasible based on evaluations from content experts, instructional design experts, and media experts, as well as receiving very positive responses from users. The effectiveness test shows a significant improvement in students’ painting skills. Therefore, the scaffolding learning-based e-book is proven to be both feasible and effective as an instructional medium in fine arts learning and has implications for supporting adaptive learning for students with intellectual disabilities.